Clinical Significance of Potential Unidentified HLA-G Isoforms Without α1 Domain but Containing Intron 4 in Colorectal Cancer Patients - Lin, Aifen; Zhang, Xia; Zhang, Rui-Li; Zhang, Jian-Gang; Zhou, Wen-Jun; Yan, Wei-Hua (Frontiers in Oncology, 2018)
The ectopic HLA-G expression in malignancies has been extensively explored and clinical significance of the molecule was widely acknowledged. Besides previously well-documented seven isoforms (HLA-G1~-G7), other novel isoforms of HLA-G have been reported but their clinical relavenace remians evaluated. In this study, lesion HLA-G expression in 379 case-matched serial section primary colorectal cancers (CRC) were evaluated with mAb 4H84 (recognizing an epitope in HLA-G α1 domain), and mAb 5A6G7 (recognizing an epitope encoded by intron 5), respectively. Data showed that HLA-G positive staining with mAbs 4H84 and 5A6G7 was 70.7% and 60.4%, respectively. When percentage of HLA-G expression detected with mAb 4H84 subtracted that with mAb 5A6G7, the difference (∆HLA-G) with negative (∆HLA-Gneg), comparable (∆HLA-Gcom) and positive (∆HLA-Gpos) were observed in 64 (16.9%), 159 (42.0%) and 156 (41.2%) cases, respectively. Noteworthy, unexpected immunostaining was observed in 44 (11.6%) lesions that no staining was detected with mAb 4H84 but positive with mAb 5A6G7 (4H84neg5A6G7pos). This staining pattern was unpredictable because all seven known HLA-G isoforms containing the α 1 domain could be recognized by the mAb 4H84. Moreover, patients with ∆HLA-Gneg had obviously better survival than those with ∆HLA-Gcom and ∆HLA-Gpos (p=0.017), and ∆HLA-G could be an independent prognostic factor for CRC patients (p=0.008). Our findings provides the first report that potential unidentified HLA-G isoforms is of distinct clinical significance in CRC patients.